Chewing Betel in Bali: An Ancient Tradition Faces Modern Times - Pramana, I Made Yogi (Bali Tourism Journal, 2023)
The customary practice of betel leaf chewing, known as Nginang, within the Balinese community, is closely linked to social rituals and the expression of hospitality towards guests. This tradition involves offering betel leaves to ancestral spirits and employing them in both healing and life cycle ceremonies. The betel leaf, areca nut, and slaked lime, constituting the core elements of this tradition, become more than mere ingredients. They transform into symbols representing the divine powers of Trimurti—Brahma, Vishnu, and Shiva. The meticulous arrangement of these components mirrors a harmonious blend of religious devotion, health benefits, and social customs. In contemporary times, the practice faces challenges, with the younger generation showing diminishing interest. However, its persistence in traditional communities highlights the resilience of cultural practices in the face of modernization. The ecological abundance of betel leaf, areca nut, and lime in Bali ensures the continuation of this tradition, not just as a cultural relic but as a living heritage. In essence, betel leaf chewing in Bali is not just a historical artifact; it's a living tradition, a cultural legacy that continues to weave through the fabric of Balinese life. It invites us to appreciate the depth and resilience of cultural practices, urging us to preserve and celebrate the diverse expressions that make each community unique.